2017
DOI: 10.1371/journal.pone.0177145
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes associated with infective stages of root-knot and lesion nematodes in soil

Abstract: Endoparasitic root-knot (Meloidogyne spp.) and lesion (Pratylenchus spp.) nematodes cause considerable damage in agriculture. Before they invade roots to complete their life cycle, soil microbes can attach to their cuticle or surface coat and antagonize the nematode directly or by induction of host plant defenses. We investigated whether the nematode-associated microbiome in soil differs between infective stages of Meloidogyne incognita and Pratylenchus penetrans, and whether it is affected by variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 51 publications
0
89
0
1
Order By: Relevance
“…In the present study, we used two rRNA genes to evaluate nematode–microbiome associations (i.e., 16S for bacteria/archaea and 18S for other microbial eukaryotes). Hypervariable rRNA gene regions have been broadly used for microbiome investigations, with previous applications in nematodes showing specific host–microbiome patterns (Derycke et al., ; Dirksen et al., ; Elhady et al., ). However, despite strict laboratory and bioinformatics protocols that were designed to maximize the recovery of nematode microbiomes, our results from free‐living marine species showed no clear patterns in host‐associated prokaryotic or eukaryotic taxa corresponding to nematode morphology, ocean region or feeding ecology (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we used two rRNA genes to evaluate nematode–microbiome associations (i.e., 16S for bacteria/archaea and 18S for other microbial eukaryotes). Hypervariable rRNA gene regions have been broadly used for microbiome investigations, with previous applications in nematodes showing specific host–microbiome patterns (Derycke et al., ; Dirksen et al., ; Elhady et al., ). However, despite strict laboratory and bioinformatics protocols that were designed to maximize the recovery of nematode microbiomes, our results from free‐living marine species showed no clear patterns in host‐associated prokaryotic or eukaryotic taxa corresponding to nematode morphology, ocean region or feeding ecology (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…Among plant parasitic nematodes, Elhady et al. () found not only that the microbiome of Meloidogyne incognita and Pratylenchus penetrans differed, but also that the soil types nematode species were exposed to had a significant effect on structuring their microbiomes. In natural habitats on Réunion Island, Meyer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, (Freckman, 1988;Wang and McSorley, 2005) or activation of specific microbial growth by the release of growth limiting nutrients (Wang and McSorley, 2005). Recent findings by Adam et al (2014) and Elhady et al (2017) confirm specific bacteria and fungi to be attached to infective stages of Meloidogyne incognita and P. penetrans in different soil types indicating an ecological role of the association. Four way interaction between fungi, oomycetes, bacteria and nematodes was supposed to increase the ARD severity when these organisms were present at the same time Mazzola and Mullinix, 2005).…”
Section: Soil Fauna Affecting Ardmentioning
confidence: 93%
“…Several metagenomic studies have reported the presence of the Malassezia genome on the surface of soil nematodes (RENKER et al, 2003;ELHADY et al, 2017), marine sponges, seawater (GAO, 2003) and corals (AMEND at al., 2012). In this study, sampling the environment as a possible source of the Malassezia yeast, and culturing of the swabs from the pool walls and water samples did not yield any Malassezia growth.…”
Section: Discussionmentioning
confidence: 99%